A study of factors affecting the length of hospital stay (LOS) of COVID-19 patients: A qualitative evidence in Iranian hospital - Rouhollah Zaboli; Mohammadkarim Bahadori; Hamid Jafari; Seyed Masood Mousavi; Sajjad Bahariniya; Parisa Mehdizadeh; Abdoreza Delavari (Journal of Education and Health Promotion, 2023)
BACKGROUND: The present study aimed to identify the administrators' and physicians' experiences and viewpoints about the factors affecting the length of stay (LOS) of COVID-19 patients and provide valid operational evidence. MATERIALS AND METHODS: The current study was carried out qualitatively and phenomenologically on experts, officials, and administrators of hospitals in 2021. Purposeful sampling was performed with the maximum diversity. To achieve a comprehensive view, snowball sampling was conducted. Twenty-one experts in the field of healthcare and emerging diseases participated in this study. Semi-structured interviews were used to collect the data. The study sites were universities of medical sciences and hospitals of the Ministry of Health of Iran. The interview questions included questions about the factors affecting the LOS and strategies for controlling the LOS of COVID-19 patients in infectious units. Text analysis was performed through the content analysis method in MAXQDA-10 software. RESULTS: Based on the experts' viewpoints, several factors affected the LOS in COVID-19 patients. These factors were divided into five clinical, preclinical, economic, social, and management subcategories. The proposed solutions included policy solutions (supportive policies, development of home care services, training and culture building, and establishment of clinical guidelines) and operational solutions (drug management, promotion of equipment and facilities, telehealth or telemedicine services, and promotion of clinical and support processes). CONCLUSION: One of the main tasks of hospital administrators is identifying the factors affecting the reduction of LOS. Among these factors, clinical and management factors in the hospital are more important and need more planning and attention by hospital officials.